2020
DOI: 10.21273/hortsci14996-20
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Morphological Variables in Garlic Bulb Yield

Abstract: The objective of this work was to investigate the direct and indirect relationships of morphological variables on garlic bulb yield. The primary components of garlic bulb yield, including clove mass, number of cloves per bulb, and bulb diameter and bulb length, are the variables that affect garlic bulb yield directly. Leaf length and growth of a secondary bulb had a negative correlation to garlic bulb yield. Growth of a secondary bulb also had a negative correlation with the number of cloves per bulb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Determination coefficients above 0.70 are considered high. Authors such as Silva et al, 2017b, Teodoro et al, 2015, Oliveira et al, 2018, and Oliveira et al, 2020 have also found coefficients of determination higher than 0.70. 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination coefficients above 0.70 are considered high. Authors such as Silva et al, 2017b, Teodoro et al, 2015, Oliveira et al, 2018, and Oliveira et al, 2020 have also found coefficients of determination higher than 0.70. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the presence of multicollinearity, all variables evaluated in the path analysis can be included, but a constant (k = 0.05) must be added to the diagonal of correlation matrix to solve this problem. The method used by Oliveira et al, 2020 for a garlic trail analysis study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tem sido relatada a existência de relação direta entre a demanda hídrica e teores de nutrientes no solo (Oliveira et al, 2020b). Neste sentido, o estudo da influência da frequência de irrigação e doses de fósforo, pode fornecer subsídios para escolha da melhor forma de condução da lavoura e, consequentemente, contribuir para melhorar a eficiência na absorção deste nutriente.…”
Section: Introductionunclassified